The Use Of Interaction Strategies To Enhance Willingness To Communicate Among Thai Efl Students - Ekkapon, Phairot (2020)
This quasi-experimental study was conducted to investigate (i) the effectiveness of interaction strategies known collectively as IS in enhancing willingness to communicate (WTC) of the Thai EFL eleventh-grade students, (ii) the interaction effect between teaching methods and levels of English proficiency, and (iii) the students' experiences in the use of the IS in the classroom. Two intact classes of the student participants in School A (N=67) and School B (N=65) in the experimental and control groups were taught using the IS and non-IS lesson plans respectively for four weeks. All student participants responded to pretest and posttest of WTC scale before and after the intervention. Purposive sampling was used to select six student participants with three levels of English proficiency in the experimental group for an individual semi-structured in-depth interview. The ANCOVA showed that the student participants' WTC posttest mean score in the experimental group was statistically significantly greater than that in the control group. The two-way ANOVA indicated that there was no significant interaction effect between teaching methods and levels of English proficiency. Using thematic analysis to analyse qualitative data, the students' experiences in the IS in the classroom were coded and grouped into three main themes, that is, (i) eliciting emotional reactions, (ii) enhancing classroom participation, and (iii) creating opportunities in learning.